The feasibility of low concentration targets: An application of FUND - Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2009)
I study the feasibility of stringent targets for stabilizing ambient greenhouse gas concentrations. Climate policy has diminishing returns, and there is therefore a maximum to what can be achieved. The success of climate policy is hampered if the terrestrial biosphere turns from a carbon sink to a carbon source because of climate change. All major countries have to reduce their emissions in order to meet the more ambitious stabilization targets. The cost of climate policy would be lower if the stabilization target can be exceeded in the interim. The EU target of 2 °C warming above pre-industrial is infeasible under almost all assumptions. A cost-benefit analysis would endorse a target of 4.5 Wm⁻² (but not much stricter than that) if all major emitters engage in abatement. Under the same condition, the median US voter would support a 3.7 Wm⁻² target (but not much stricter than that). International permit trade would encourage large developing countries to reduce emissions, but the trade flows would be substantial relative to product trade and much larger than official development aid.
Keywords: Q54; 330; international climate policy; greenhouse gas emission reduction; Klimaschutz; Internationale Umweltpolitik; Treibhausgas; Umweltschutzkosten; Welt